Analysis On the Attitude Towards Seeking Professional Psychological Help - F A Nurdiyanto; Griselda Maria Ancela Wodong; Ririn Mamiek Wulandari (Unnes Journal of Public Health, 2023)
Failure to obtain mental health assistance from professional services can lead to wider treatment gaps and serious effects. People with mental health problems are encouraged to access mental health services for early assessment and intervention to promote their psychological well-being. This study was intended to evaluate the attitude towards professional help-seeking by considering demographic factors. This research was conducted through a quantitative approach using the ATSPPH-SF as the main instrument. A total of 590 respondents (male 150, x̅ age 24,16) participated voluntarily by filling out an online survey. The result found that the highest frequency of the respondents’ attitude was in the moderate category. This study also found that the attitude towards professional help-seeking was significantly different by gender (p<0,05), but there were no differences by ethnic group (Javanese, Minahasa, Sundanese), ages, and monthly expenses (p>0,05). This study shows that many Indonesians have not relied on professionals as the main source in solving mental health problems.